A79 CHARACTERIZATION OF VIPOMA-MEDIATED INTESTINAL EPITHELIAL CELL SECRETION. (1st March 2018) - Leung, G; Elkadri, A; Murchie, R; Thoeni, C E; Muise, A
Abstract: Background: A 3-year old female with a history of chronic watery diarrhea was diagnosed with a suprarenal vasoactive intestinal peptide (VIP)-secreting neuroblastoma ('VIPoma'). Neuroblastomas are one of the most common malignancies in children aged 0–5 years, while VIP is a gastrointestinal neuropeptide that can act upon epithelial cells, neurons, and immune cells. Secretory diarrhea and hypokalemia are classic symptoms of a VIPoma, however the precise mechanism remains unknown. Aims: To define in the pathway of VIP-mediated ion secretion using intestinal organoids. Methods: Prior to diagnosis, supplemental KCl was given (3 mmol/kg) to address the low potassium. Following this, serum and stool samples were collected daily for 8 days to measure electrolyte (Na +, K +, Cl - ) levels and stool osmolal gap. Intestinal organoids were cultured from a sigmoid colon biopsy of a non-inflamed control patient. Organoids were labelled with calcein AM dye and assessed every 12 min for 1–2 hrs by microscopy, with luminal ion secretion assessed by the increase in organoid size over time. Results: The patient's serum potassium levels were consistently below the normal range and the stool osmolal gap was <50 mmol/L (indicative of secretory diarrhea). Supplemental KCl increased [K + ] in the blood but failed to improve the diarrhea. VIP levels at the time of diagnosis were 7.3X above the upper limit of the normal range. To test this in vitro, VIP was applied to intestinal organoids in vitro; concentrations above the normal range (10 -10 and 10 –9 M) but not within the normal limits (10 –11 M) induced a swelling response in normal human enteroids. This swelling was completely abolished in isotonic K + -deficient buffer, and dependent on Ca + for maximal effect. The use of the non-specific potassium channel blocker tetraethylammonium chloride (TEA; 1–10 mM) did not significantly reduce the organoid swelling response when applied 30 min prior to VIP stimulation. Conclusions: Increased intake of potassium improved serum [K + ] levels but did not relieve the diarrheal symptoms. A significant swelling response occurs in intestinal organoids when stimulated with VIP in the absence of a neural or immune network. More studies are needed to further characterize the signalling pathway and ion channels through which this secretory response occurs in the intestinal epithelium. Funding Agencies: CIHRHelmsley Charitable Trust